Edukasi 5S dalam Upaya Continuous Improvement Melalui Audit 5S Pada PT Inti Ganda Perdana (IGP) - Rusmiati, Emi; Ambarwati, Laksmi; Santoni, Dede (Journal of Community Services in Sustainability, 2023)
The good industrial development in Indonesia gave rise to new industries aimed at increasing production capacity. Efforts are made to increase capacity by carrying out continuous improvement. One that can be done is to provide an understanding of 5S and 5S audits. PT IGP has so far implemented 5S, but sometimes employees still need to be reminded of the 5S implementation. Therefore it is necessary to carry out 5S audits and internalize 5S understanding for employees and management. This Community Service Activity (PkM) was carried out. Beginning with observation, problem identification, literature study, data collection and processing, as well as analysis and giving recommendations, then conclusions and suggestions are made. The audit results show that the average audit score is 3.1 out of a scale of 4. Meanwhile, the score that needs attention is the sort, which is 2.79. From the results of the audit, internalization of 5S understanding was carried out through the creation of a 5S pocket book to increase 5S understanding for employees. By giving a pocket book there is an increase in understanding before internalization is carried out with a pretest with an average score of 60.625 after being given an understanding of 5S, the score becomes 80.625.